Avian flight - Videler, John J. (Oxford ornithology series ;, 2005)
This accessible reference covers all the main aspects of arial locomotion by birds including sections on the history of bird flight study, aerodynamics, fuctional morphology, evolution, kinematics, physiology, energetics and the costs of flight.